Eliciting Public Discourse of SE Tool Providers in a Study on Requirements Process Debt - A Different Shade of Gray - Freire, Sávio; Maciel, Rita S. P.; Mendonça, Manoel; Leite, Julio Cesar (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
Context: Grey literature (GL) has grown in importance in software engineering (SE) research. The area has recognized Q&A sites, blogs, and online professional magazines as rich sources of SE knowledge. These sources’ formality (and reliability) varies with the amount of review their content goes through. Some sources are light-shaded, others are very shady. Web content can increase knowledge gained through empirical studies, but it can be a shady source of information. This work explores a particular type of web content, SE solution providers’ discourse, a different shade of grey, to study previous findings on requirements process debt. Aims: To introduce a method to elicit the solution providers’ public discourse on the causes of requirements process debt. Strategy: To propose and evaluate the method based on its application by eighteen elicitors, performing a quantitative and qualitative analysis of the content retrieved by the elicitors. Results: We have positive confirmation of the method’s adequacy and replicability, indicating that it can elicit public discourse to confirm previous results published in the technical literature about the causes of requirement process debt. Conclusion: The results anchor the idea that one can systematically elicit web-extracted data within a defined domain.